2011
DOI: 10.1103/physrevlett.106.203001
|View full text |Cite
|
Sign up to set email alerts
|

Classical Dynamics of Laser-DrivenD3+

Abstract: A classical model of the triatomic D₃⁺ molecule subjected to an intense, few-cycle laser pulse is introduced. The model is capable of describing the laser-induced correlated motion of both electrons and nuclei in three dimensions, and allows us to follow the motion of the two electrons and three deuterons from the initial field-free state, during the pulse, and until the bond breaking into the final fragments. By averaging over many trajectories, we calculate the relative yields of the ionization and dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 35 publications
7
37
1
Order By: Relevance
“…The FMD model has been shown to produce stable, quasiclassical ground-state configurations for all atoms with charge number Z 94 [62,63], and has been applied extensively to atomic and molecular collisions [64][65][66][67][68][69][70][71][72]. Beginning with the application to laser-driven helium [73,74], it has also been successfully used for the description of laser-atom interaction [75][76][77][78][79], laser-molecule interaction [80][81][82][83], and laser-cluster interaction [84]. We mention that in [84], where the FMD model was also used to simulate the laser-driven dynamics of the six valence electrons in a single Xe atom, good qualitative agreement with experimentally measured ionization yields was found.…”
Section: Introductionmentioning
confidence: 99%
“…The FMD model has been shown to produce stable, quasiclassical ground-state configurations for all atoms with charge number Z 94 [62,63], and has been applied extensively to atomic and molecular collisions [64][65][66][67][68][69][70][71][72]. Beginning with the application to laser-driven helium [73,74], it has also been successfully used for the description of laser-atom interaction [75][76][77][78][79], laser-molecule interaction [80][81][82][83], and laser-cluster interaction [84]. We mention that in [84], where the FMD model was also used to simulate the laser-driven dynamics of the six valence electrons in a single Xe atom, good qualitative agreement with experimentally measured ionization yields was found.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of that work was on the ionization channels, namely the fragmentation of the transient D 3 2+ and D 3 3+ ions. Classical model calculations of these fragmentation processes have been reported recently [14], while quantum mechanical treatment is still a challenge. In parallel, Alexander et al [15] reported photodissociation of D 3 + that was allowed to vibrationally cool by storage in an electrostatic trap.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of FTI in atoms, Manschwetus et al have observed the formation of excited H * atoms following strong-field laser fragmentation of H 2 [21] (see also N 2 [22], Ar 2 [23,24], and theory for D 3 + [25]). In conjunction with these experiments, we have performed measurements of excited D * atoms from D 2 that we report here.…”
Section: Introductionmentioning
confidence: 99%